Development of a Novel Loop-Mediated Isothermal Amplification Method to Detect Guiana Extended-Spectrum (GES) β-Lactamase Genes in Pseudomonas aeruginosa - Takano, Chika; Seki, Mitsuko; Kim, Dong Wook; Gardner, Humphrey; McLaughlin, Robert E.; Kilgore, Paul E.; Kumasaka, Kazunari; Hayakawa, Satoshi (Frontiers in Microbiology, 2019)
Infections caused by multidrug-resistant Pseudomonas aeruginosa in hospitalised patients are often fatal, and nosocomial infections caused by Guiana extended-spectrum (GES) β-lactamase-producing strains are of growing concern. Several genotypes of the GES β-lactamase gene (blaGES) include a single missense mutation, a change from G to A at nucleotide position 493 (G493A) that changes glycine to serine; the mutant enzyme exhibits carbapenemase activity. Rapid and reliable identification of drug-resistance is important in clinical settings; however, culture methods remain the gold standard. Conventional and real-time PCR cannot identify carbapenemase-producing genotypes, and direct DNA sequencing is essential. We established a novel loop-mediated isothermal amplification (LAMP) method to detect various genotypes of blaGES and another LAMP method to discriminate carbapenemase genotypes of blaGES. We evaluated the two assays using clinical P. aeruginosa strains. Two primer sets targeting blaGES (GES-LAMP) and the point mutation (Carba-GES-LAMP) were designed and evaluated for specificity and sensitivity. The detection limit of the GES-LAMP method was assessed using purified DNA and DNA-spiked clinical samples (urine, sputum, and blood). To determine the clinical usefulness of the methods, we used different (genotypically and phenotypically) P. aeruginosa clinical isolates, collected from diverse geographical locations between 2003 and 2012. The novel LAMP assay targeting blaGES was highly specific. The detection limit was 10 DNA copies per reaction; the assay was 10-fold more sensitive than conventional PCR. The LAMP assay detected blaGES with high sensitivity in all DNA-spiked samples; PCR did not detect blaGES in blood samples. The GES-LAMP method correctly detected the 5 isolates containing blaGES among the 14 isolates tested. Using these isolates, we confirmed that our Carba-GES-LAMP method of detecting point mutations correctly identified the two blaGES positive organisms with carbapenemase activity. To the best of our knowledge, this is the first report of the GES β-lactamase gene detection assay using the LAMP method. Our new assays effectively detect blaGES and critical unique mutations.